169k views
4 votes
Simplify the following expression.2(0.5x - 3)2-[?]x2 – [ ]x + [ ]-

Simplify the following expression.2(0.5x - 3)2-[?]x2 – [ ]x + [ ]--example-1
User Tssch
by
5.3k points

1 Answer

4 votes

1st blank = 0.25

2nd blank = 3

3rd blank = 9

Step-by-step explanation:
\begin{gathered} \text{Given: (0.5x - 3)}^2 \\ \\ To\text{ simplify the expression we expand} \end{gathered}

Using distributive property:


\begin{gathered} (0.5x-3)^2\text{ = (0.5x - 3)(0.5x - 3)} \\ =\text{ 0.5x (0.5x - 3) - 3(0.5x - 3)} \\ =\text{ 0.5x(0.5x) -3(0.5x) -3(0.5x) - 3(-3)} \end{gathered}
\begin{gathered} =0.25x^2\text{ - 1.5x - }1.5x\text{ + 9} \\ =0.25x^2\text{ - 3.0}x\text{ + 9} \\ =0.25x^2\text{ - 3x + 9} \\ \\ \text{first balnk = 0.25} \\ \text{second blank =3} \\ \text{third blank = 9} \end{gathered}

User PDA
by
5.1k points